HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KECEPATAN LARI DENGAN HASIL LOMPAT JAUH PADA SISWA SMA NEGERI 1 BENGKALIS - Ranianti, Ranianti; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, the problem in this study originated from the observation that the author found in SMA Negeri 1 Bengkalis, long jump result is yet to get maximum results. The purpose of this study was to determine the relationship of leg muscle explosive power and speed to run with the results of the long jump at SMA Negeri 1 Bengkalis. This type of research is correlational. The population in this study were students of SMAN 1 Bengkalis numbering 131 people using purposive technique next to the sample in this study was 20 people The population in this study were students of SMAN 1 Bengkalis which amounts to 131 people using purposive technique next to the sample in this study was 20 people consisting of male students only . To get the research data used tests standing broad jump, 40 yard running speed with the results of the long jump. Data were analyzed by simple and multiple product moment. Based on data analysis found that the results obtained from the explosive power leg muscle have a relationship with the results of the long jump. From the results obtained running speed have a relationship with the results of the long jump. There is a relationship jointly between leg muscle explosive power and speed to run against the results of the jump.Keywords : Explosive Power Leg Muscle, Speed, Long Jump